Searching for Solace - Mahmoud Dhaouadi (International Institute of Islamic Thought, 1997)
Searching for Solace consists of two parts, two appendixes, and a section displaying documents and photos of Yusuf Ali and those with whom he had contact. The author devotes the first part to A. Yusuf Ali's life and his service to the British. He was born in 1872 in Surat, western India, into the Bohra mercantile community, whose members trace their Muslim ancestry to the effons of preachers sent by the FaJimid caliphs in Cairo. Ali was sent to Bombay for his education. While there, he attended the new school of the Anjuman-e-Islam and, subsequently, a missionary school named after its founder, John Wilson. He was barely eight or nine years old when he left home. Classes were taught in both Urdu and English. When he was fifteen, Ali left Wilson's school and entered its senior section, Wilson College, which was affiliated to the University of Bombay. Sherif thinks that Ali's education in the Anjuman school helped him resist the cultural onslaught of the dominant British colonizer. Ali arrived in Britain in 1891 to study law at St. John College. He eventually became one of its best students, which predisposed him to work in the Indian Civil Service (ICS), a much prized career. His first appointment, on 23 January 1896, was assistant magistrate and collector in Saharanpur, India. After a few years in India, he returned to Britain in 1905 for a leave. While there, he married Teresa Mary Shalders. Sherif thinks that his marriage to an English woman symbolizes Ali's desire to establish a bridge between India and the West. But this marriage ended in divorce in 1912 following his wife's an exttamarital affair. Their children were left in her custody. The affairs of his children are considered to be one reason that pushed Ali to resign from ICS. But his loyalty to the British empire remained sttong. When Britain declared war on Germany in August 1914, he reaffirmed his commitment: "I am prepared and shall be pleased to volunteer to temporary service, in any capacity in which I can be useful on account of the War" (p. 32). Ali's strong commitment to the British was based on his belief that India could learn a lot from Britain. But he also had a strong faith in Islam as a religion and civilization that could contribute much to the West. This should have been among the strong reasons that motivated him to ttanslate the Qur'an into English. His Interpretation of the Qur'an has made him famous among Muslim speakers of English throughout the world. The author underlines a number of factors that helped Ali achieve this great work: "A troubled domestic life, ear ...